Bone Regenerative Potentiality of Nanostructured Biphasic Hydroxyapatite /Tricalcium Phosphate Prepared from Eggshell as a Bone Graft in Vivo - Karrar A. Zaker; Ziad H. Delemi; Ammer A. Taqa (University of Mosul, College of Dentistry, 2020)
Aims: to evaluate the biological response to nano sized biphasic hydroxyapatite and tricalcium phosphate synthesized from eggshell. Materials and methods: Egg shell burned in furnace at 1000 C° for 1 hour. The part of resultant powder was treated chemically with phosphoric acid to form HA, other part of heated egg shell treated with nitric oxide and di-ammonium hydrogen phosphate to form TCP then the two products mixed mechanically at ratio 80%/20% (HA/TCP). The mixture turned to nanoparticles via mechanical attrition and sieving membrane and sent for TEM, the resultant material characterization checked by FTIR spectroscopy. Two defects of 2 mm prepared in the femoral bone of 20 rabbits one filled with prepared material (group A) and the other left empty as negative control (group B). Results: greater bone formation was founded in group A where statistically significant. Conclusions: biphasic hydroxyapatite and tricalcium phosphate nano particles synthesized from eggshell is effective in bone regeneration and could be used as bone substitute derived from source of no economic value.